Free Thoughts on Religion, the Church, and National Happiness Bernarda Mandeville’a jako lekcja anatomii natury ludzkiej w praktyce - Droś, Agnieszka (In Gremium. Studies in History, Culture and Politics, 2022)
The article attempts to present Bernard Mandeville’s lessons on the anatomy of human nature in practice, i.e. the practical application of knowledge about human passions by clever clergymen-politicians. Based mainly on Free Thoughts on Religion, the Church, and National Happiness, it has been proven that religion in the views of the author of this work is part of a system that is to keep society together by basing to the fear of an invisible power. At the same time, religion becomes an instrument used for constant abuse, struggle for power and material goods by clergy who skillfully manipulate human weaknesses. Religion ceases to play the role of a link between God and the faithful, and its role is reduced to conducting dirty politics. Mandeville’s approach to this topic reminds us of the need for a thorough and objective analysis of our behavior, thanks to which a person will not only be able to understand himself, positively affect the condition of his own physical and mental health, but also protect himself from unnecessary conflicts. The problem of not knowing oneself is central to Bernard Mandeville’s thought.